Kepatuhan PT.Giri Palma Dalam Memenuhi Wajib Pajak - Muhammad Rayhan Maulidan; Indrawati Yuhertiana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study examines tax compliance at PT. Karya Giri Palma Furniture, one of the leading manufacturing companies in Indonesia, concerning tax regulations. Employing a qualitative descriptive approach, the study explores management understanding of tax regulations, tax reporting systems, and factors influencing tax compliance levels within the company. Findings indicate that factors such as business profile, industry dynamics, and psychological factors play crucial roles in taxpayer compliance behavior.